PENGGUNAAN METODE BLACK BOX TESTING (BOUNDARY VALUE ANALYSIS) PADA SISTEM AKADEMIK (SMA/SMK) - Puji Astuti (Faktor Exacta, 2018)
By using this applied system, then the process of academic data collection in SMA / SMK easier and faster in data processing, because this applied system there are buttons that help for data processing and there are columns for searching data and others , And by using Black Box Testing (Boundary Value Analysis) data entry function can be accurate, appropriate functional and in making report of student, teacher and rapar more effective and efficient,Keywords: Academic, System, Black Box Testing